2008
DOI: 10.1080/13506120802193720
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity of penetrance in familial amyloid polyneuropathy, ATTR Val30Met, in the Swedish population

Abstract: Transthyretin (TTR) familial amyloid polyneuropathies (FAP) are autosomal dominant devastating afflictions. They were first described in Portugal, later in Japan and Sweden and are now recognized worldwide. The TTR Val30Met mutation is the most common, and depending on the geographic origin, a wide variation in age at onset of the disease is observed. In Europe, northern Sweden is the second most prevalent area of the disease, and a late age of onset of 56 years has been reported. The present study aims to est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
105
0
9

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 154 publications
(120 citation statements)
references
References 21 publications
6
105
0
9
Order By: Relevance
“…23 For a patient with FAP, the age at which symptoms develop depends on the genetic mutation, the patient's origin, and the penetrance of the disease. [24][25][26] Other factors directly related to transplantation have also been implicated in the early development of amyloidotic changes in domino liver recipients. First, the presence of amyloid fibers in the graft may trigger the disease.…”
Section: Discussionmentioning
confidence: 99%
“…23 For a patient with FAP, the age at which symptoms develop depends on the genetic mutation, the patient's origin, and the penetrance of the disease. [24][25][26] Other factors directly related to transplantation have also been implicated in the early development of amyloidotic changes in domino liver recipients. First, the presence of amyloid fibers in the graft may trigger the disease.…”
Section: Discussionmentioning
confidence: 99%
“…In Japan, Met30 families with early onset neuropathy were initially identified in 2 limited areas (Arao district and Ogawa village) with a penetrance of 80% 10. Late onset (>50 years) TTR‐FAP Val30Met (LateMet30) is widely distributed throughout Japan11 as well as in northern Sweden, where penetrance is lower 12. FAP patients of French descent are divided into 2 groups depending on their pathogenic TTR mutation.…”
mentioning
confidence: 99%
“…19 At present, there is no explanation for the important difference in penetrance estimation between countries. [10][11][12] One might speculate that a mitochondrial polymorphism could account for at least part of this difference if the at-risk alleles had different frequencies among countries. The results of our study on the Portuguese and the Swedish families favor this hypothesis as the estimated frequency of the at-risk allele was much higher in the Portuguese (0.69) than in the Swedish (0.32) populations.…”
Section: Discussionmentioning
confidence: 99%
“…9 In a previous work, we showed that important differences in disease expression, and in particular in penetrance estimation, exist among countries. [10][11][12] The cumulative risks by age 70 years were estimated to be 91% in Portuguese carriers, 64% in French carriers, and 36% in Swedish carriers.…”
Section: Introductionmentioning
confidence: 99%